Development of a Special Nutritional Supplement Based on Cabbage Powder as the Main Ingredient - Wu Xianghan; He Siyuan; Liu Yang; Zhang Shunjun; Guo Guangyao; Li Zhonghua; Li Dan; Mo Linfang; Wang Jinxiu (BIO Web of Conferences)
Food materials such as cabbage have therapeutic effects for improving certain diseases. Through specific formulations and technologies like drying, concentration, and ultrafine grinding, a type of nutritional supplement based on cabbage powder as the main ingredient has been developed. These supplements are presented in convenient forms, such as fruit and vegetable slices, noodles, hawthorn cakes, or rice flour, catering to different functional needs. Testing has shown that these products meet relevant food hygiene standards and have a shelf life of over 12 months, rendering them a potential reference for developing functional foods.